Expression of a Chimeric Gene Encoding Insecticidal Crystal Protein Cry1Aabc of Bacillus thuringiensis in Chickpea (Cicer arietinum L.) Confers Resistance to Gram Pod Borer (Helicoverpa armigera Hubner.) - Das, Alok; Datta, Subhojit; Thakur, Shallu; Shukla, Alok; Ansari, Jamal; Sujayanand, G. K.; Chaturvedi, Sushil K.; Kumar, P. A.; Singh, N. P. (Frontiers in Plant Science, 2017)
Abstract Domain swapping and generation of chimeric insecticidal crystal protein (ICP) is an emerging area of insect pest management. The lepidopteran insect pest, gram pod borer (Helicoverpa armigera H.) wreaks havoc to chickpea crop affecting production. Lepidopteran insects were reported to be controlled by Bt (cryI) genes. We designed a plant codon optimized chimeric Bt gene (cry1Aabc) using three domains from three different cry1A genes (Domain I, II and III from cry1Aa, cry1Ab and cry1Ac, respectively) and expressed it under the control of a constitutive promoter in chickpea (cv. DCP92-3) to assess its effect on gram pod borer. A total of six transgenic chickpea shoots were established by grafting into mature fertile plants. The in vitro regenerated organogenetic shoots were selected based on antibiotic kanamycin monosulphate (100 mg/L) with transformation efficiency of 0.076%. Three transgenic events were extensively studied based on gene expression pattern and insect mortality across generations. Protein expression in pod walls, immature seeds and leaves (pre and post flowering) were estimated and expression in pre-flowering stage was found higher than that of post flowering. Analysis for the stable integration, expression and insect mortality (detached leaf and whole plant bioassay) led to identification of efficacious transgenic chickpea lines. The chimeric cry1Aabc expressed in chickpea is effective against gram pod borer and generated events can be utilized in transgenic breeding programme.